Increasing Knowledge, Attitudes, Skills, and Glucose Control in Type-2 Diabetic Patients through EMAS Interventions - Andriyanto, Arief; Rekawati, Etty; Rahmadiyah, Dwi Cahya (Department of Nursing, Faculty of Medicine, Diponegoro University, 2019)
Background: Diabetes Mellitus (DM) is a chronic and non-communicable disease that has serious impacts. Previous studies have focused on a single intervention in the management of DM. Therefore, EMAS (education, nutrition management, physical activities, and stress management) interventions are proposed to convey the pillars of diabetes mellitus as endorsed by the Indonesian Ministry of Health.Purpose: This study aimed to analyze the effects of EMAS interventions on the knowledge, attitudes, skills, and glucose control in patients with type-2 DM.Methods: This study used a pretest-posttest quasi-experimental design without control groups. The samples were 86 diabetic patients recruited using a purposive sampling technique. The EMAS interventions were conducted for six months and eight sessions (October 2018 to March 2019). The EuroQoLfive-dimensional (EQ-5D) questionnaire was used to collect the data, and the paired t-test was used for data analysis. Results: The results showed that there were significant differences in the knowledge, attitudes, skills (p=0.001), and glucose control (p=0.04) of type 2 diabetes mellitus after the implementation of EMAS interventions. Conclusion: EMAS interventions significantly increased the knowledge, attitudes, and skills in patients with type 2 diabetes to behave healthier to control their blood sugar. Community nurses can use EMAS intervention for the management of DM among diabetic patients.